ARMScope – the versatile platform for scanning probe microscopy systems - Świadkowski Bartosz; Piasecki Tomasz; Rudek Maciej; Świątkowski Michał; Gajewski Krzysztof; Majstrzyk Wojciech; Babij Michał; Dzierka Andrzej; Gotszalk Teodor (Metrology and Measurement Systems, 2020)
Scanning probe microscopy (SPM) since its invention in the 80’s became very popular in examination of many different sample parameters, both in university and industry. This was the effect of bringing this technology closer to the operator. Although the ease of use opened a possibility for measurements without high labour requirement, a quantitative analysis is still a limitation in Scanning ProbeMicroscopes available on the market. Based on experience of Nano-metrology Group, SPM still can be considered as a tool for quantitative examination of thermal, electrical and mechanical surface parameters. In this work we present an ARMScope platform as a versatile SPM controller that is proved to be useful in a variety of applications: fromatomic-resolution STM (Scanning TunnellingMicroscopy) toMulti-resonance KPFM (Kelvin Probe force microscopy) to commercial SEMs (Scanning electron microscopes).